Nanorobotic System iTRo for Controllable 1D Micro/nano Material Twisting Test - Haojian Lu; Wanfeng Shang; Xueyong Wei; Zhan Yang; Toshio Fukuda; Yajing Shen (Scientific Reports, 2017)
Abstract In-situ micro/nano characterization is an indispensable methodology for material research. However, the precise in-situ SEM twisting of 1D material with large range is still challenge for current techniques, mainly due to the testing device’s large size and the misalignment between specimen and the rotation axis. Herein, we propose an in-situ twist test robot (iTRo) to address the above challenges and realize the precise in-situ SEM twisting test for the first time. Firstly, we developed the iTRo and designed a series of control strategies, including assembly error initialization, triple-image alignment (TIA) method for rotation axis alignment, deformation-based contact detection (DCD) method for sample assembly, and switch control for robots cooperation. After that, we chose three typical 1D material, i.e., magnetic microwire Fe74B13Si11C2, glass fiber, and human hair, for twisting test and characterized their properties. The results showed that our approach is able to align the sample to the twisting axis accurately, and it can provide large twisting range, heavy load and high controllability. This work fills the blank of current in-situ mechanical characterization methodologies, which is expected to give significant impact in the fundamental nanomaterial research and practical micro/nano characterization.